Collected poems - Kinnell, Galway 1927-2014 (Houghton Mifflin Harcourt, 2017)
"The definitive collection of poems from Pulitzer Prize winner, MacArthur Fellow, and National Book Award winner Galway Kinnell. "It's the poet's job to figure out what's happening within oneself, to figure out the connection between the self and the world, and to get it down in words that have a certain shape, that have a chance of lasting." ...Galway Kinnell. This long-awaited volume brings together for the first time the life's work of a major American voice.In a remarkable generation of poets, Galway Kinnell was an acknowledged, true master. From the book-length poem memorializingthegrit,beauty, and swarming assertionof immigrantlifealonga lower Manhattan avenue, to searing poems of human conflict andwar, to incandescentreflections on love,family, and the natural world...including "Blackberry Eating," "St. Francis and the Sow," and"After Making Love We Hear Footsteps"...tothe unflinchingly introspective poems of his later life, Kinnell's work lastingly shaped the consciousness of his age. Spanning 65 years of intense, inspired creativity, this volume, with its inclusion of previously uncollected poems, is the essential collection for old and new devotees of a "poet of the rarest ability. who can flesh out music, raise the spirits, and break the heart." (Boston Globe)"...